2023
DOI: 10.3389/ffgc.2023.1209232
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of above ground biomass and soil organic carbon in the forests of Nepal under climate change scenario

Rajesh Malla,
Prem Raj Neupane,
Michael Köhl

Abstract: IntroductionMany factors, such as climate, topography, forest management, or tree/forest attributes, influence soil organic carbon (SOC) and above-ground tree biomass (AGTB). This study focuses on assessing relationship between various predictor variables and response variables (SOC and AGTB) in the perspective of climate change scenario. The study was conducted throughout in Nepal using forest resource assessment data (2010–2014).MethodsOur study applied a random forest model to assess the status of SOC and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 101 publications
0
2
0
Order By: Relevance
“…Lewis et al [79] found an increase in AGB in African tropical forests with precipitation during the driest nine months of the year and a decrease during the wettest three months of the year. Malla et al [71] reported a positive effect on AGB of the precipitation of the driest month and the maximum temperature of the warmest month in the forests throughout Nepal. The positive effect of precipitation during the driest month suggests that ensuring water availability during periods of rainfall can contribute to increased growth in the growing season [36], resulting in higher AGB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lewis et al [79] found an increase in AGB in African tropical forests with precipitation during the driest nine months of the year and a decrease during the wettest three months of the year. Malla et al [71] reported a positive effect on AGB of the precipitation of the driest month and the maximum temperature of the warmest month in the forests throughout Nepal. The positive effect of precipitation during the driest month suggests that ensuring water availability during periods of rainfall can contribute to increased growth in the growing season [36], resulting in higher AGB.…”
Section: Discussionmentioning
confidence: 99%
“…The partial plot function under the :randomForest" package version 4.7.1.1 in the R 4.3.0 software was used, following the methodology proposed by [70] Friedman (2001). Partial dependence plots are commonly employed to examine the linearity, non-linearity, or other intricate relationships between predictors and response variables [71].…”
Section: Statistical Model and Analysismentioning
confidence: 99%